Protection of the Acquired Rights towards the Administration Authority in withdrawing the Administrative Decisions. - Saeed, Dana AbdulKareem; Faraj, Dlshad Fatah (Journal of Legal and Political Studies, 2019)
In this research, entitled (Protection of acquired rights towards the administration authority to withdraw its decisions), we discussed the extent of administration authority in the withdrawal of administrative decisions and its effect on the personal acquired rights, thus we talked about the legitimate administrative decisions that start the moment of birth of the acquired right from the date of issuance and the illegal administrative decisions That starts at the moment of the acquired right by the leaving of the legal period for challenge. That administration does not have the right to withdraw its decision after this period because it is immune from any withdrawal and becomes a legal source to create the personal acquired rights. and so, it is adopted by jurisprudence and the administrative judiciary in each of the France, Egypt and Iraq. As we found in the content of this research that the administration does not have the absolute authority to withdraw its decisions, but there is a set of legal or judicial controls that impose upon to that authority, in order to provide a mount of legal protection for the personal rights acquired, but with regard to guarantees to protect the acquired rights, we find that the legality principle and non- prejudice to the acquired rights are as most succeed and important guarantees for the personal acquired rights. Then the principle of legality means that if the administration carries out a particular activity or conduct, it has a duty to work within the law boarder to abide by it, In addition, the administrative jurisprudence does not recognize the administration legitimacy actions if it caused by to broke the principle of non-prejudice to the personal affects of legal actions.
Keywords: administration authority; right to withdraw; immunity; challenge; judicial controls